The Fusion Fuel Cycle Simulator — towards integrated dynamic process simulation of fusion fuel cycles - Teichmann, Tim; Schwenzer, Jonas; Day, Christian; Matsunaga, Yoshinao; McGrady, John; Kume, Yoshifumi; Baus, Colin; Konishi, Satoshi; Dashliborun, Amir Motamed (Fusion engineering and design, 2025)
Kyoto Fusioneering in collaboration with Canadian Nuclear Laboratories, under the auspice of Fusion Fuel Cycles Inc. is developing the Fusion Fuel Cycle Simulator (FFCSim), a modular and flexible fusion fuel cycle design and simulation tool that can be used to provide a dynamic, physics-based and closed-loop simulation of holistic fusion fuel cycles. The FFCSim aims to enable accurate quantitative prediction of individual unit performances, support dynamic and steady state simulation, as well as the integration of process chains up to full fuel cycle scale. This paper will introduce the high-level concepts of the tool, its modeling basis and implementation, as well as select verification cases. [Display omitted] •The Fusion Fuel Cycle Simulator (FFCSim) is introduced as a new tool for fusion fuel cycle simulation.•The FFCSim allows for dynamic, physics-based and closed-loop process simulations.•High level concepts, the modeling basis and implementation are discussed.•Selected validation cases are described and discussed.